Maximum principles for parabolic systems coupled in both first-order and zero-order terms - Chiping Zhou (International Journal of Mathematics and Mathematical Sciences)
Some generalized maximum principles are established for linear second-order parabolic systems in which both first-order and zero-order terms are coupled.